2002
DOI: 10.1111/j.1582-4934.2002.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly effective techniques in computerized dental tissue morphometry

Abstract: The effectiveness of computer‐aided morphometry is greatly dependent of the capabilities of the software platforms, but the literatutre provides only information about the measurement methods and thier medical interpretation. The purpose of our work is to create a link between the technical algorithm and the medical significance, by a detialed description of measurement procedures, accompained by the interpretation of thier results. The developmed techniques operate at a pixel level, by deriving a full benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Accordingly, Schuh et al25 and Xavier et al12 recently observed that grit blasting with Al 2 O 3 particles resulted in rough Ti surfaces contaminated with Al 2 O 3 . In the present study, we quantified Al 2 O 3 residues using Zeiss KS400, a software based on mathematical operations capable of modifying the values of the image pixels to be analyzed by the computer 13, 26, 27. We observed that sand blasting procedure produced a surface with higher roughness and Al 2 O 3 residues occupying an average area of 9.72% of these surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Schuh et al25 and Xavier et al12 recently observed that grit blasting with Al 2 O 3 particles resulted in rough Ti surfaces contaminated with Al 2 O 3 . In the present study, we quantified Al 2 O 3 residues using Zeiss KS400, a software based on mathematical operations capable of modifying the values of the image pixels to be analyzed by the computer 13, 26, 27. We observed that sand blasting procedure produced a surface with higher roughness and Al 2 O 3 residues occupying an average area of 9.72% of these surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…They also served for computing the nucleo-cytoplasmic ratio (CNA j /CCA j ) of each cell. Our technique for image processing was derived from the key principles in quantitative morphological analysis of cells proposed in our previous work [18].…”
Section: Resultsmentioning
confidence: 99%
“…Towards this end, we considered three types of cells, as follows: normal -resembling the superficial cells in the cervical smears (in the remainder of the text referred to as superficial cells), normalresembling the intermediate cells in the cervical smears (in the remainder of the text referred to as intermediate cells) and tumoral. In the first part of the study we extracted the individual morphometric features of 1500 cells, for each cell j measuring the cytoplasmic area CCA j and nuclear area CNA j , respectively, by applying a technique adapted from our previous work [18]. Starting from this numeric information we noted that the measured cells could be linearly separated in two classes, normal and tumoral.…”
Section: Introductionmentioning
confidence: 99%
“…The approach proposed in this work for the analysis of evolving fibroblasts is founded on our experience in computerized morphometry [ 34 , 35 ]. The technique used [ 35 ] has been considerably improved in order to process large sets of digital images in relatively short time intervals.…”
Section: Discussionmentioning
confidence: 99%